Determination of distribution coefficient: a critical review. (1st January 2014) - Pathak, Pankaj; Singh, D.N.; Pandit, G.G.; Rakesh, R.R.
Geomaterials (soils and rocks) exhibit peculiar physical, chemical, mineralogical and biological properties, which influence their interaction with the contaminant(s) to a great extent. This interaction can be quantified by employing a parameter 'Distribution coefficient', kd, which plays an important role for determining sorption and desorption characteristics of the contaminant when it interacts with geomaterial(s). Apart from the soil specific properties, kd depends upon the pH of the pore solution, ambient temperature, type and concentration of competitive ions, the presence of microorganisms, etc. Usually, batch, column and lysimetric tests are employed for determining kd . However, it has been observed that kd varies in a wide range and the methodologies adopted for its determination have their limitations and shortcomings. As such, these methodologies are being critically evaluated by researchers so that they may be modified or replaced by new ones, which are easy to adopt and yield reliable results quickly. With this in view, efforts have been made in this paper to highlight the importance and role of parameters that influence determination of kd . Further, details of the studies related to determination of kd as reported by earlier researchers and a commentary on the guidelines for determining it are also presented in this paper.